A internacionalização da pós-graduação na UFMT pela via do ingresso regular de estudantes estrangeiros - Alegre, Elaine Silva (2019)
The beginning of postgraduate studies at UFMT dates from 1996, with the creation of the Master's degree course in Ecology and Biodiversity Conservation at the institution. Over the years, the implementation of new Programs at the University became more complex and new demands are required to maintain and advance the PPGs in the scientific world. In this regard, only good performance and the counterpart of results to regional, local and national communities are insufficient. It is crucial to prove its magnitude, with the awakening of the interest and recognition of other nations regarding national publications, especially for high-status publications, which are evaluators of the best academic and scientific productions in the world, in the various areas of knowledge. This context of meeting international standards of excellence in knowledge promotion is intrinsic to national insertion in global economic and technological development. Therefore, the country must be capable of producing useful knowledge on a global scale, if it wishes not to be put aside to international technological and economic remains, but also to diplomatic articulation in the transmission of knowledge generated and the provision of quality education also to foreign students. That mentioned, this study reveals the degree of internationalization of postgraduate knowledge at the Federal University of Mato Grosso, regarding the regular admission of international students to Masters and Doctorate courses of the referred Higher Education Institution, until the second semester of 2019. To this end, we bring a theoretical framework on Education in Brazil and in the World. We also present the relationship of UFMT and the International Cooperation Networks of which it is a member; the PPGs entry requirements; the diagnosis of the admission of foreign students to the aforementioned University, revealing, in addition, the profile of the international students that appear in it as masters and doctoral students.